2010
DOI: 10.1097/pas.0b013e3181f0b05a
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Budding as a Strong Prognostic Indicator in Invasive Ampullary Adenocarcinomas

Abstract: Prognostication of invasive ampullary adenocarcinomas (AACs) and their stratification into appropriate management categories have been highly challenging owing to a lack of well-established predictive parameters. In colorectal cancers, recent studies have shown that tumor budding confers a worse prognosis and correlates significantly with nodal metastasis and recurrence; however, this has not been evaluated in AAC. To investigate the prevalence, significance, and clinical correlations of tumor budding in AAC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 43 publications
(59 reference statements)
4
79
1
Order By: Relevance
“…This is in accordance to previous studies in colorectal cancer, ampullary cancer, rectal cancer where it has been associated with lymph node metastasis and has been correlated with distance of invasion beyond the lamina propria. 5,6,16,19 This corroborates the possibility of tumor budding's ability in defining the biologic aggressiveness of the tumor and serving as an index for the metastatic potential in OSCC. This association with depth of invasion has also been confirmed recently by Almagush et al 12 recently in tongue cancer.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This is in accordance to previous studies in colorectal cancer, ampullary cancer, rectal cancer where it has been associated with lymph node metastasis and has been correlated with distance of invasion beyond the lamina propria. 5,6,16,19 This corroborates the possibility of tumor budding's ability in defining the biologic aggressiveness of the tumor and serving as an index for the metastatic potential in OSCC. This association with depth of invasion has also been confirmed recently by Almagush et al 12 recently in tongue cancer.…”
Section: Discussionsupporting
confidence: 74%
“…5,6,10,11 Furthermore, presence of intratumoral budding, that is, presence of tumor budding in preoperative biopsy specimens has also been described, which has demonstrated a strong linear correlation with peritumoral budding at the invasive front in the postoperative specimens opening another venue in its utility for prognostic determination. 20 Cervical lymph node metastasis has been considered as one of the major prognostic factor in patients with OSCC.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Multiple series have shown that increased tumor budding is associated with lymph node metastasis, distant metastasis, and recurrence in colorectal adenocarcinomas [15,16]. Similar studies have also shown a similar relationship in adenocarcinomas of the ampulla [21], esophagus [22,23], and pancreas [24]. However, very little research has been performed evaluating tumor budding in GAC [18,25,26].…”
Section: Accepted Manuscriptmentioning
confidence: 79%
“…Given the wide variety of different methods employed in both colorectal carcinoma and upper gastrointestinal malignancies [15,16,18,21,22,24] that provide largely compatible results, it is reasonable to hypothesize that a single standardized method could be applied to carcinomas throughout the luminal gastrointestinal tract. Another potential pitfall in the assessment of tumor budding assessment is the need to ensure an acceptable level of interobserver variability.…”
Section: Accepted Manuscriptmentioning
confidence: 99%